The Power of Social Pensions - Wei Huang; Chuanchuan Zhang (Institute of Labor Economics (IZA), 2016)
This paper examines the impacts of social pension provision among people of different ages. Utilizing the county-by-county rollout of the New Rural Pension Scheme in rural China, we find that, among the age-eligible people, the scheme provision leads to higher household income (18 percent) and food expenditure (10 percent), lower labor supply (6 percent), and better health (11-14 percent). In addition, among the age-ineligible adults, the pension scheme shifts them from farming to non-farming work, lowers insurance participation rate, but does not change income, expenditure or health significantly. Finally, among the children aged below 15, the pension scheme leads to more pocket money received, more caring from grandparents, improved health, and higher schooling rate.
Keywords: E21; H55; I38; O22; 330; pension; health; elderly